Experiences of Digital Communication in Developing Literacy and School Readiness through Deep Learning in Early Childhood Education - Wichitra Yasya; Asima Oktavia Sitanggang; Apriyanti Widiansyah (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study explores how digital communication contributes to literacy development and school readiness through the lens of Deep Learning in early childhood education in Indonesia. Using Media Richness Theory as the theoretical lens, this study employed a qualitative phenomenological methodology to explore how digital communication through the use of a tablet-based learning application foster literacy development and school readiness through Deep Learning in early childhood education. Data were collected through classroom observations, in‑depth interviews and open‑ended questionnaires distributed to teachers, principals, and school operators of early childhood centers in Bekasi that had adopted a of tablet-based digital learning program. Thematic analysis showed that multimodal features and immediate feedback from the application enhanced children’s engagement and motivation, while infrastructural barriers such as limited devices and uneven teacher competence restricted implementation. Evidence of Deep Learning was observed in children’s persistence, creativity, collaboration, and intrinsic motivation, with some transferring digital concepts into everyday contexts. School readiness improved both cognitively, through literacy and numeracy gains, and socio‑emotionally, through patience, turn‑taking, and confidence. The findings highlight the importance of combining digital tools with conventional pedagogy, ensuring equitable access to devices, strengthening teacher professional development, and involving parents to reinforce home–school connections. Digital communication, when intentionally integrated, can serve as a pathway to Deep Learning and school readiness in early childhood education.